(untitled) (Res Medica, 2014)
• Title: Geriatrics (Guidelines in Medicine — Vo.1) Authors: A.N. Exton-Smith, P.W. Overstall. Publishers: MTP Press Limited. Pages 344. Publication Date: 1979 • Title: The M.R.C.G.P. Examination. Authors: A.J. Moulds, T.A. Bouchier Hayes & K.H.M. Young. Publishers: M.T.P. Press Limited, International Medical Publishers. Pages 131. publication Date: November 1978. Price: £4.95 • Title: Local Analgesia — 2nd edition. Author: Dr. Clive Jolly. Publishers: H.K. Lewis & Co. Ltd., London. Pages: 152 (illusr. — 19) Publication date: 1979. Price: £5.00 nett